(untitled) (Al-Farooq Journal of Sciences, 2026)
This study addresses the topic of Public Policy-Making in Libya: The Problem of Institutional Coordination and Its Impact on the Effectiveness of Public Decision-Making. It aims to analyze the reality of public policy-making in Libya, identify the nature of coordination among the institutions and actors involved in the policy-making process, and examine the impact of the level of institutional coordination on the quality, consistency, and speed of public decision-making, as well as the ability to monitor its outcomes. The study adopted a descriptive-analytical approach by describing the reality of public policy-making and the manifestations of institutional coordination in Libya. The study concluded that weak institutional coordination represents one of the factors affecting the effectiveness of public policy-making in Libya. The multiplicity of decision-making centers, overlapping jurisdictions, weak information exchange, and the absence of some permanent coordination mechanisms contribute to increasing the likelihood of conflicting decisions, delays in decision-making and implementation, duplication of procedures and tasks, waste of resources, and difficulties in determining responsibilities and ensuring accountability. The study recommends developing institutional and regulatory frameworks for coordination, clarifying jurisdictions and responsibilities, establishing permanent institutional coordination mechanisms, strengthening information exchange and communication among institutions, developing government information systems, and supporting integration among central and local institutions and the various actors involved in public policy-making. It also recommends strengthening monitoring and evaluation mechanisms and fostering an institutional culture based on cooperation and integrated government action.